PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA CARA TUBUH MENGOLAH UDARA BERSIH - Ardi Nata Nugroho; Tatang Muhajang; Nurlinda Safitri (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE EFFECT OF THE USE OF PROBLEM BASED LEARNING MODEL ON THE RESULTS OF LEARNING SUBTEMA HOW THE BODY CREATES CLEAN AIRThe Effect of Using Problem Based Learning Model on Learning Outcomes of the Subtheme How the Body Processes Clean Air. Thesis of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, 2021. This research is a quasi-experimental research. This study aims to determine the difference in learning outcomes of the subtheme of How the Body Processes Clean Air through the use of Problem Based Learning Models for Class VB students and Conventional Learning Models for Class VA students. This research was conducted at Bangka 03 State Elementary School, Bogor City, Class VA and Class VB from July to August in the odd semester of the 2021/2022 academic year. Calculation of N-Gain Problem Based Learning model is 81 with high criteria, and the conventional model value is 70 with medium criteria. So that the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the conventional model. Researchers conducted a normality test with the Liliefors test, both samples were normally distributed because the values for both samples were smaller than Ltable. In the Problem Based Learning class group, the value of Lcount Ltable is 0.139 0.161, in the control class group the Lcount Ltable is 0.058 0.161. Then in the homogeneity test, the data is homogeneous because Fcount Ftable, the value is 1.35 1.88. Furthermore, in hypothesis testing, it was found that tcount of 14.59 was greater than ttable of 2.00404, indicating that H0 (zero hypothesis) was rejected and Ha (alternative hypothesis) was accepted. Based on the research above, it can be stated that there are differences in the learning outcomes of the first learning through Problem Based Learning and Conventional Learning Models..